LOST IN TRANSLATION? ASSESSING THE IMPORTANCE OF LANGUAGE SKILLS AND CULTURAL AWARENESS IN SPECIAL FORCES ADVISORY EFFORTS - Sobchak, Frank. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Richard Shultz.; Committee: Abigail Linnington, and Patrick Howell.; Keywords: International relations, Military studies, and Military history.